Estimating Elasticity of Substitution in CES Production Function: Examining Different Nesting Structures and EU Regions - Vedunka Kopecna; Milan Scasny; Lukas Recka (Charles University in Prague, Institute of Economic Studies (IES), 2020)
Elasticity of factor substitution is one of the key parameters of any computational general equilibrium model. Despite a wide use of this model in a policy analysis, there are a few estimates of the elasticity, with almost none for transition economies in Europe. To fill this gap, we estimate the elasticity of substitution between Capital, Labour, Energy and Material in the constant elasticity of substitution (CES) production function. We use a non-linear estimation technique to derive these elasticities for the whole economy and for five different sectors, for the EU as a whole and for its two sub-regions. We find that Cobb-Douglas and the Leontief production functions do not fit the data better than more flexible CES specification, and after evaluating several multiple KLEM nesting structures of the CES production function we conclude that KL-E and KL-EM nesting structures fit the data best in both EU regions and for the most economic sectors. The economy-wide factor substitution elasticity complies to the one reported in the literature, however, its magnitude varies across sectors, and it is much larger for the energy-intensive sectors. The elasticities also differ between the EU economies in the West and in the East, although their magnitude is converging in more recent years. We recommend a set of the specific elasticities to be used in the impact modelling and conclude that the estimates based on more recent data and that are region-specific should be used in CGE-based policy applications.
Keywords: C51; D24; 330; Elasticity of substitution; Constant elasticity of substitution (CES); nesting structure; KLEM production function; Central and Eastern European Countries